Cadeias referenciais: o objeto de discurso e sua evolução na progressão textual - Silva, Silvia Regina Neves da (2007)
This study focuses on the constitution of referential chains (RCs), arising from the installation and the establishment of the referent in the text, as well as from strategies of referential progression which provide its evolution. The main hypothesis is that the referent, constituted as object-of-discourse and marked by constitutive instability, is subjected to evolution in the RC, due to the referential mechanisms operating in the text. This thesis arises from the pressupositon that the referent is installed and established in the text, displaying a network in the RC. The study offers evidences that in the RC the object-of-discourse is outlined and constitutes co-textual and contextual semantic relations, which, from retakens and remissions, proceed the categorization of its referential status and provide its continuity in the textual progression, making it possible its evolution. The analysis of written and oral texts, literary and non-literary, is based on the application of a categorial referential framework, in the light of Textual Linguistics of social-discoursive and cognitive orientation. The quantitative and qualitative results show that: (1) the most relevant mechanism of first reference is the activation of the object-of-discourse, arising from a basis referent established in the text or only implicited, displaying a unique RC or other linear or multilinear RCs; the most relevant in the referential progression is the ellipsis; (2) the most relevant anaphoras in the referential progression are the direct ones, that constitue linear RCs and maintain the correference throughout the text; the most appropriate mechanisms regarding this type of anaphora are lexical repetition, pronominalization, ellipsis and, in a lesser degree, lexical recategorization; (3) the atributive expressions and the referentials in atributive usage fulfill the function of detaling the referent by the adduction of attributes and by recategorizations of argumentative value, providing meanings that can or can not be homologated; they also contribute to enhance the evolution of the referent in narratives sequences with descriptive mixture, and in procedural descriptive sequences; (4) the most relevant mechanism of first mention for the evolution of the object-of-discourse is the activation of new referents; the most relevant of referential progression are the adduction of attributes and lexical recategorizations. Finally, the results show that the object-of-discourse can exibit different nature and ways of evolution in accordance with the discourse domain, the intention of the enunciator, the composition of textual gender, and the types of textual sequences and mechanisms of referentiation involved